Sustainable Beauty in Indonesia: The Role of Attitude in Mediating the Impact of Environmental Knowledge and Perceived Eco-Friendly Quality on Purchase Intention - Arin Widyaningtyas; Aflit Nuryulia Praswati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of environmental knowledge, green perceived quality, and brand image on purchase intention toward environmentally friendly beauty products, with attitude as a mediating variable. Central Java was selected due to its growing interest in sustainable products and rising environmental awareness, making it a relevant context for green consumer behavior research in Indonesia. Using a quantitative method, data were collected from 185 respondents via an online survey, though self-selection bias may limit generalizability. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed for analysis. Results show that environmental knowledge and brand image significantly influence purchase intention, while green perceived quality affects purchase intention indirectly through attitude, indicating a potential lack of consumer clarity on green product quality. Attitude serves as a key mediator, underscoring the importance of positive consumer perceptions. These findings suggest that effective marketing strategies should focus on environmental education, brand strengthening, and clearer communication of product sustainability to boost consumer confidence and intention to purchase green beauty products.